On the maximum mean subtree order of trees. (October 2021) - Cambie, Stijn; Wagner, Stephan; Wang, Hua
Abstract: A subtree of a tree is any induced subgraph that is again a tree (i.e., connected). The mean subtree order of a tree is the average number of vertices of its subtrees. This invariant was first analyzed in the 1980s by Jamison. An intriguing open question raised by Jamison asks whether the maximum of the mean subtree order, given the order of the tree, is always attained by some caterpillar. While we do not completely resolve this conjecture, we find some evidence in its favor by proving different features of trees that attain the maximum. For example, we show that the diameter of a tree of order n with maximum mean subtree order must be very close to n . Moreover, we show that the maximum mean subtree order is equal to n − 2 log 2 n + O ( 1 ) . For the local mean subtree order, which is the average order of all subtrees containing a fixed vertex, we can be even more precise: we show that its maximum is always attained by a broom and that it is equal to n − log 2 n + O ( 1 ) .